Factors Affecting Internal Auditor Performance - Eka Sariningsih; Iing Lukman; Yulistia Devi; Iis Safitri (eCo-Buss, 2023)
This study aims to determine the impact of control position, self-efficacy, role conflict, and time-budget pressure on auditor performance in BPKP's Lampung provincial representative office. This research is a quantitative research and has the nature of raw data. The data collection technique used in this study was the distribution of questionnaires. The population in this study included auditors working in the BPKP's Lampung provincial office, up to 75 auditors. The sample of this study is determined by census method or saturation sampling method, that is, all members of the population are used as samples. The data analysis method of this study used SPSS version 26 program for multiple linear regression analysis. performance at the same time. Partially, the variables of inspection location, self-efficacy, and time-budget pressure had a significant effect on auditor performance, while the variable role conflict had no effect on auditor performance in the BPKP representatif office in Lampung Province.